Adsorption Equilibrium and Thermodynamic Analysis of CO2 and CH4 on Qinshui Basin Anthracite - Xidong Du; Tengfei Wu; Fulong Sun; Zhenkun Hou; Zhenjian Liu; Liang Huo; Yu Hao; Yuan Zhao (Geofluids)
Adsorption isotherms of CH4 and CO2 on Qinshui Basin anthracite were obtained at the temperatures of 283 K, 303 K, and 323 K using the gravimetric method. The feasibility of the displacement of CH4 by injecting CO2 on this anthracite was verified by calculating the selectivity factor of CO2 over CH4 (αCO2/CH4), adsorption affinities, and thermodynamic properties of CH4 and CO2. Results show that the values of αCO2/CH4 are more than 4.0. Henry’s constant (KH) of CH4 is smaller than that of CO2, and CH4 has a weaker affinity with coal surface. As temperature improves, KH of CO2 and CH4 decrease. Gibbs free energy change (ΔG) and surface potential (Ω) of CO2 are more negative than those of CH4, indicating that CO2 adsorption on anthracite is more spontaneous and favorable. The absolute values of Ω and ΔG of CH4 and CO2 increase with pressure rises. Isosteric heat of adsorption (Qst) of CH4 is lower than that of CO2. With increasing loading, Qst and entropy loss (ΔS) of CH4 decrease, while Qst and ΔS of CO2 increase. The higher ΔS of CO2 reveals that the adsorbed CO2 molecules constitute a more stable rearrangement than CH4 molecules. High temperature reduces ΔS of CH4 and CO2.